INVENTARISASI ARSITEKTUR BANGUNAN CAGAR BUDAYA KANTOR POS SEMARANG (Memikirkan Kembali Peluang Fungsi Kantor Pos di Era Digital) - R. Siti Rukayah; Sudarmawan Juwono (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: During the Dutch colonial period, Daendeles (1808) built a 1000km postal highway from Anyer - Panarukan. Now the road is known as the pantura (north coast route). The main function is to facilitate communication between regions controlled by Daendeles. One of the buildings that influenced the construction of the postal highway was the first post office in Batavia (1746) and the second post office in Semarang (1750). In the city of Semarang, along with the development of the city to the south and the existence of road infrastructure towards the kingdom of Mataram (Surakarta and Jogjakarta), several branch post offices were built in the Bangkong area and the Post Office Jalan Dr. Wahidin. The building is the center of postal services and operations in the city of Semarang and its surroundings. However, along with the development of the postal industry process, it has pushed service rooms to be more efficient, resulting in a reduction in the need for workspaces which results in a lot of space that can be used for other functions. This opportunity to revitalize the old post office building can be integrated with the potential of the Old Town area which has been developed as a mainstay tourism destination for the city of Semarang. Taking into account this potential, the purpose of this paper is to map and inventory the architectural potential of the Semarang post office which is very urgent to do. The method used is to conduct observations and interviews in a structured manner. The focus of the study is on the potential of architecture, including architectural space and character, as well as the potential of the existing environment or area. The result of the building inventory to preserve that not only focuses on the physical building but also how the activities in it are still attached to the function of the building.Abstrak: Pada masa colonial Belanda, Daendeles (1808) membangun jalan raya pos sepanjang 1000km dari Anyer - Panarukan dan kini dikenal dengan jalur pantura. Fungsi utama adalah memperlancar komunikasi antar daerah yang di kuasai Daendeles. Salah satu bangunan yang berpengaruh terhadap dibangunnya jalan raya pos adalah Kantor pos pertama di Batavia (1746) dan Kantor pos kedua di Semarang (1750). Di Kota Semarang seiring dengan perkembangan kota ke arah Selatan dan telah adanya infrastruktur jalur jalan kearah kerajaan Mataram (Surakarta dan Jogjakarta) maka dibangunlah kantor pos cabang di kawasan Bangkong dan Kantor pos jalan Dr. Wahidin. Bangunan tersebut menjadi salah satu tulang punggung pelayanan dan operasional pos di wilayah Kota Semarang dan sekitarnya. Namun seiring dengan perkembangan proses industri pos telah mendorong ruang pelayanan semakin efisien sehingga terjadi pengurangan kebutuhan ruang kerja yang mengakibatkan banyak ruang yang bisa dimanfaatkan untuk fungsi lain. Peluang ini dapat diintegrasikan dengan potensi kawasan Kota Tua telah dikembangkan sebagai ruang publik dan destinasi pariwisata andalan Kota Semarang. Dengan memperhatikan adanya potensi tersebut tujuan paper ini adalah melakukan mapping dan inventarisasi potensi arsitektur kantor pos Semarang yang sangat mendesak untuk dilakukan. Metode yang dilakukan adalah melakukan survey lapangan dan wawancara secara terstruktur. Adapun fokus kajian adalah pada potensi arsitektur mencakup ruang dan karakter arsitektur, serta potensi lingkungan atau kawasan yang ada. Hasil dari inventarisir bangunan adalah upaya untuk melestarikan yang tidak hanya berfokus pada fisik bangunan saja tetapi juga bagaimana aktivitas di dalamnya masih tetap melekat dengan fungsi bangunannya.